Study on the Cost of Establishing Community Pharmacy in Lalitpur and the Role of Banks - Bajracharya, Omi; Upadhyay-Dhungel, Kshitiz (Banking Journal, 2012)
DOI: http://dx.doi.org/10.3126/bj.v2i2.6622 Banking Journal, Volume 2 (Issue 2) 48-63